Dynamics of Changes in Preschool Teacher Preparation Programs (1950-2010) - Kucina, Aina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Each period is characterized by its specific features which are the base for forming learning values, educational process principles for higher education, educational aims for future teachers. The development of pedagogy subject as an academic discipline is a prime example of political and social developments of society impact.The preparation of professional pre-school teacher and the implementation of the curriculum are topical problems in previous and current Latvian socio-economic and educational context. Changes in preschool teacher preparation program design and implementation are given an opportunity to compare, try and select the most valuable to fit the today’s child's personality development.